Combining Autologous and Prosthetic Techniques: The Breast Reconstruction Scale Principle - Taglialatela Scafati, Salvatore (Plast Reconstr Surg Glob Open, 2017)
BACKGROUND: The latissimus dorsi (LD) flap remains a good option for immediate or delayed breast reconstruction. The main limitation of this flap is the small volume provided. To improve the reconstructed breast volume, the LD flap is usually combined with a breast implant. Recently, fat grafting to the LD flap was described to maximize flap volume and obtain a totally autologous breast reconstruction. We report our experience with hybrid breast reconstruction using both breast implants and fat-enriched latissimus dorsi (FELD) flaps. METHODS: Between 2013 and 2016, 74 patients underwent breast reconstruction with FELD flaps only or FELD flaps combined with a breast implant. The LD flap was harvested as previously described. Donor sites for fat harvesting were chosen according to each patient’s natural fat distribution. Fat was harvested, centrifuged, and injected into the LD flap. After fat grafting, breast sizers were employed to determine the final breast volume when the addition of an implant was indicated. RESULTS: Good cosmetic outcomes were achieved in all cases, with a mean follow-up of 2.1 years. No patients had cancer reoccurrences. Four patients experienced a seroma of the LD donor site, 1 had a breast hematoma, and 1 developed Baker grade III capsular contracture. One year postoperatively, a clinically relevant area of fat necrosis was observed in 1 patient and was surgically treated. Additional fat grafting sessions were required in 3 cases. CONCLUSION: In elected cases, a FELD flap alone or in combination with a small implant is a valuable technique for breast reconstruction surgery.